Design Of Storm water Drainage system For Beit JalaCity - ABUHMEDA, WESAM; SADOQ, KHALED (جامعة بوليتكنك فلسطين - كلية الهندسة - مساحة, 2015)
The disposal of storm water in streets and roads creates major traffic and environmental problems . Sewage facilities in many Palestinian cities do not exist , The storm water has been seeping into the streets and roads through the overflows causing serious problems . Beit Jala is such as Bethlehem district cities , do not contains storm water drainage system . The accelerated development and grow of Beit Jala city has led to change in the hydrological and geomorphological features . all of the areas of Beit Jala city do have not a natural drainage outlet . Heavy rainfall causes storm water to collect in low areas and flood streets and walk way . Rapid growth has decreased the open area available for percolation and rain water has greatly increased the runoff to low laying areas . In view of this prevailing condition , Drainage system in Beit Jala city would have a new characteristic and development of storm water drainage system is very necessary to drain excess water from streets . In this project a trial was made to design a storm water drainage system for Beit Jala city, and we find that the drainage system must contain four main and six submain lines as main trunks that make drainage for water in the rain fall events . These main trunks cover a large percentage area of Beit Jala . And they ara efficient in minimizing traffic problems .
no of pages 67, 28249 , مساحة 10/2014 , in the store
Keywords: Storm water Drainage system